Evaluation of good practices in restaurants in Joinville, Santa Catarina, Brazil - Renata Carvalho Oliveira; Rosinei de Assis da Silveira; Rafaella Mafra (Universidade do Estado do Rio de Janeiro, 2020)
Introduction: The increase in eating out of home is directly related to the expansion of food service. Because of this expansion, studies are needed to evaluate hygienic-sanitary conditions and good practices in food services. Objective: Evaluate good food handling practices in restaurants in Joinville-SC, Brazil. Method: Data collection performed through the application of good practice checklist for food service, part of the Normative Resolution No. 3 of the Directorate of Sanitary Surveillance of Santa Catarina State, Brazil, in accordance with RDC No. 216 / 2004 of the Brazilian Health Surveillance Agency. Results: Checklist was applied to 30 restaurants, only one was classified as fully satisfactory, with an adequacy index of 81.8%; two were classified as satisfactory, with an average of 53.0% adequacy; and the remaining 27 restaurants obtained an adequacy index below 50.0%, being classified as unsatisfactory. Conclusion: Considering the results, it is necessary to adopt operational and corrective measures to control the critical points. These must be carried out and reinforced by nutritionists who work in restaurants, aiming to reduce non-conformities and, consequently, the risks of foodborne diseases.